Risk and Protective Factors for the Mental Wellbeing of Deployed Healthcare Workers During the COVID-19 Pandemic in China: A Qualitative Study - Khoo, Vicky Poh Hoay; Ting, Rachel Sing-Kiat; Wang, Xinli; Luo, Yuanshan; Seeley, Janet; Ong, Jason J.; Zhao, Min; Morsillo, Julie; Su, Chunyan; Fu, Xiaoxing; Zhang, Lei (Frontiers in Psychology, 2021)
Background: Though many literatures documented burnout and occupational hazard among healthcare workers and frontliners during pandemic, not many adopted a systemic approach to look at the resilience among this population. Another under-studied population was the large numbers of global healthcare workers who have been deployed to tackle the crisis of COVID-19 pandemic in a less resourceful regions. We investigated both the mental wellbeing risk and protective factors of a deployed healthcare workers (DHWs) team in Wuhan, the epicenter of the virus outbreak during 2020. Method: A consensual qualitative research approach was adopted with 25 DHWs from H province through semi-structured interviews after three months of deployment period. Results: Deductive thematic coding with self-reflexivity revealed multi-layered risk and protective factors for DHWs at the COVID-19 frontline. Intensive working schedule and high-risk environment, compounded by unfamiliar work setting and colleagues; local culture adaptation; isolation from usual social circle, strained the DHWs. Meanwhile, reciprocal relationships and “familial relatedness” with patients and colleagues; organizational support to the DHWs and their immediate families back home, formed crucial wellbeing resources in sustaining the DHWs. The dynamic and dialectical relationships between risk and protective factors embedded in multiple layers of relational contexts could be mapped into a socio-ecological framework pre-, peri- and post-deployment. Conclusions: Our multidisciplinary study highlights the unique social connectedness between patient-DHWs; within DHWs team; between deploying hospital and DHWs; and between DHWs and the local partners. We recommend five organizational strategies as mental health promotion and capacity building for deployed workers to build a resilient network and prevent burnout at the disaster frontline.